Pembangunan Rice Milling Unit Untuk Menjamin Harga Gabah Petani dan Kebutuhan Beras - I Ketut Arnawa; Ni Putu Sukanteri; Menardo Denis Villanueva (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Farmers do not get certainty of grain price. The construction of Rice Milling Unit guarantees the price of grain received by farmers. The main objective of the study is to analyze the feasibility of the construction of Rice Milling Unit from the aspect of grain availability, rice needs and financial aspects. The study uses a descriptive method, the study was conducted in Badung Regency. Data were collected by questionnaires and interviews. Data analysis of the feasibility of the aspect of grain availability and rice needs was analyzed descriptively, and the feasibility of the financial aspect was analyzed using investment criteria, namely Net Present Value (NPV) Net Benefit Cost Ratio (Net B / C), Internal Rate of Return (IRR) and Payback period. The results of the study found that from the aspect of grain availability and rice needs it was feasible, from the financial aspect it was feasible with an NPV of Rp. 171,931,999.193, Net B / C 1.2900, IRR 25.05% and Payback Period 1.44. The construction of Rice Milling Unit by the government guarantees the price of grain to farmers and the community's rice needs are met with stable prices.